Valuation Model Bias and the Scale Structure of Dividend Discount Returns - Michaud, Richard O.; Davis, Paul L. (Journal of Finance, 1982)
Richard O. Michaud, Paul L. Davis, Valuation Model Bias and the Scale Structure of Dividend Discount Returns, The Journal of Finance, Vol. 37, No. 2, Papers and Proceedings of the Fortieth Annual Meeting of the American Finance Association, Washington, D.C., December 28-30, 1981 (May, 1982), pp. 563-573